2016
DOI: 10.4049/jimmunol.1502658
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Ectosomes Reduce NK Cell Function

Abstract: Platelet (PLT) transfusions are potentially life saving for individuals with low PLT numbers; however, previous work revealed that PLT transfusions are associated with increased infection risk. During storage, PLT intended for transfusion continuously shed ectosomes (Ecto) from their surface, which express immunomodulatory molecules like phosphatidylserine or TGF-β1. Recently, PLT-Ecto were shown to reduce proinflammatory cytokine release by macrophages and to favor the differentiation of naive T cells toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…TGF‐β1 downregulates expression of activating NK cell receptors (ie, NKG2D and CD16) as well as multiple cytokine mediators/enzymes, resulting in diminished NK cell‐killing capacity . Consistent with the view that platelet‐derived TGF‐β1 promotes metastasis by limiting NK cell functions, previous studies have shown that platelet‐specific deletion of TGF‐β1 significantly limits metastatic potential . One straightforward hypothesis that could couple the observations of Lucotti et al with these previous findings is that TXA 2 is critical to support platelet‐mediated secretion of TGF‐β1 from α granules.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…TGF‐β1 downregulates expression of activating NK cell receptors (ie, NKG2D and CD16) as well as multiple cytokine mediators/enzymes, resulting in diminished NK cell‐killing capacity . Consistent with the view that platelet‐derived TGF‐β1 promotes metastasis by limiting NK cell functions, previous studies have shown that platelet‐specific deletion of TGF‐β1 significantly limits metastatic potential . One straightforward hypothesis that could couple the observations of Lucotti et al with these previous findings is that TXA 2 is critical to support platelet‐mediated secretion of TGF‐β1 from α granules.…”
mentioning
confidence: 66%
“…22,23 Consistent with the view that platelet-derived TGF-β1 promotes metastasis by limiting NK cell functions, previous studies have shown that platelet-specific deletion of TGF-β1 significantly limits metastatic potential. 19,24 One straightforward hypothesis that could couple the observations of Lucotti et al with these previous findings is that TXA 2 is critical to support platelet-mediated secretion of TGF-β1 from α granules. Alternatively, studies in which the TXA 2 pathway is targeted in the context of platelets lacking TGF-β1 could also reveal novel mechanisms coupling TXA 2 -mediated platelet functions to metastasis independent of TGF-β1 secretion.…”
Section: Metastatic Tumor Cells Have Been Shown To Possess Strong Pro-mentioning
confidence: 90%
See 2 more Smart Citations
“…While less is known about PLT‐derived factors as TRIM mediators, emerging data strongly suggest that PLTs and PLT‐derived factors have important immunomodulatory potential . For instance, PLT‐derived microparticles are capable of inducing both immune cell suppression and activation . PLTs themselves may play important roles in modulating immune cell response in both health and disease, suggesting that residual PLTs found in RBC products likely contribute to immunomodulation.…”
Section: Proposed Mechanismsmentioning
confidence: 99%